KRITIK KEPEDULIAN SOSIAL ADLER DAN IKHLAS TERHADAP PERILAKU PRO-SOSIAL MANUSIA MODERN - Arman Marwing (UIN Sayyid Ali Rahmatullah Tulungagung, 2016)
The rise of pro-social behavior in the modern era in diverse forms at all levels of the social good, individual, group, corporation deemed to have not succeeded in creating a growing social transformation. The concept of sincere look at the failure of transformation caused by tilting motif of a transcendental interest [254] Kontemplasi, Volume 04 Nomor 02, Desember 2016to dwell on the motives toward selfishnes. Meanwhile, the concept of social awareness accused Gemeinschaftsgefuhl or failure due to strong motive personal excellence, as well as the existence of discrepancies between the motives of social awareness in a way or purpose (result) is expected. Social care emphasizes the importance of the way (method) and the objectives are verified by the results in the form of the success of all people in the community are ideal. Despite differences realm that limits the extent to which a behavior can be tested, sincere and social care have the same value that prosocial behavior can not be understood as a response to the positive consequences as well as the paradigm behavioristis Skinnerian, but the liberation of man from the attributes of affirmation of personal excellence.Keywords: Social concern, Ikhlas, Pro-social